Vector-Valued Ces¿Ro Summable Generalized Lorentz Sequence Space - Oğur, Oğuz; Duyar, Birsen Sağır (My University, 2017)
The main purpose of this paper is to introduce Cesaro summable generalized Lorentz sequence space C1[d(v; p)]. We study some topologicproperties of this space and obtain some inclusion relations.
Keywords: Matematik; İstatistik ve Olasılık